HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN HYGIENE PENJAMAH MAKANAN DIKANTIN SDN SEKECAMATAN KAMPAR - Misky Madrdhatillah Madrdhatillah (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2019)
Food is a basic human need that is needed and requires a good food handler, and the importance of food hygiene and safety for health so as not to be contaminated, sought in the process of processing until the food presentation is done as well as possible so as to produce healthy food to benefit the body. The purpose of this study was to determine the relationship of knowledge and attitudes with food handlers hygiene in the canteen (SDN) of the Elementary Schools in Kampar sub-district in 2018. The cross sectional study design, this research was carried out on 21-28 July 2017 in the canteen (SDN) of the Elementary School of Kampar District. The sample in this study was hygiene food handlers in the canteen (SDN) of Elementary Schools in the District of Kampar, amounting to 50 people. The sampling technique is random sampling. The instrument used was a questionnaire. The data obtained were analyzed by chi square test, the significance level was 95%. The results of the bivariate analysis found that there was a significant relationship between knowledge and hygiene of food handlers in SDN canteen in Kampar sub-district obtained p value = 0,000, and there was a significant relationship between attitude and hygiene sanitation of food handlers obtained p value = 0.038. For food handlers Increase awareness and pay attention to the safety of processed and served food to consumers and the importance of food hygiene and safety so as not to be contaminated, so as to produce healthy food in the Kampar sub-district.